A REVIEW ON IDENTIFICATION OF CRACKS IN ALUMINIUM CANTILEVER BEAM THROUGH FINITE ELEMENT ANALYSIS (ANSYS) - Hunka, Nitin (Innovare Journal of Engineering and Technology, 2015)
In past era of time, a wide range of researches and study works have been made and concluded by various researchers/ authors in the development of techniques for the identification of cracks (structures). It is verified by the various studies that the dynamic behavior of any structure changes causes presence of any defects such as cracks in a body of structure. Therefore, it is vital to identify the defects in structures and its components; which is generally called crack and analyze them. The present work conducted to review analytical as well as experimental investigation/studies conducted by the researchers for the identification of cracks in an aluminum cantilever beam with rectangular cross section. The main purpose of this review is to examine and to verify the extent of harm to the beam (structure) with the critical location of the crack in a cantilever beam.